PENGUJIAN USABILITY SISTEM INFORMASI PELAYANAN RUKUN WARGA MENGGUNAKAN USE QUESTIONNAIRE - Esron Rikardo Nainggolan; Susafa’ati Susafa’ati (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2018)
In order to create complacency and success of an information system that has been created, a test is needed, one of them is usability testing on the system to be implemented. This testing is done by analyzing the usability aspects of a system. Usability aspects to be tested including Usefulness, Satisfaction, and Ease of use. The purpose of this research is to determine the acceptance of usability web-based citizen services system by measuring the dimensions of usefulness, satisfaction, and ease of use. This research used a testing method with USE Questionnaire which consists of 30-Question. This research is a descriptive quantitative research conducted on Rusunawa RW 014 Pesakih by survey method. The test results showed the average variable value is 4.18 and was in the Interval of Assessment "Good (B) / High (T)" which can be interpreted website-based citizen services system has a good usability value and this information system can be implemented in Rusunawa Pesakih.